Toward the impacts of Indian drama serials on Bangladeshi family system: an overview of people’s perception - Md. Abdullah Al Helal (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
Nowadays Indian drama serials are very popular in Bangladesh. Young, old even children are interested to watch it. These people watch and imitate the life style portrayed in these daily soaps. That is gradually eating up our traditional and enriched cultural norms and values. Study revealed that these Indian drama serials provoke sexual behavior, instigate pre and extra martial affair, educate criminal activity, originate eve teasing, and nurture conflict between family members. Study also disclosed that these daily soaps impose Hinduism culture in every sphere of life of Bangladeshi people. This study was carried on 100 families of Dhaka city corporation area on the basis of random sampling. At the end the paper suggested some remedial measures that are indispensably needed to save our viewers from the negative consequences of Indian drama serials and stop cultural intrusion.